2021
DOI: 10.1061/(asce)ir.1943-4774.0001547
|View full text |Cite
|
Sign up to set email alerts
|

Development of Aerial Photos and LIDAR Data Approaches to Map Spatial and Temporal Evolution of Ditch Networks in Peat-Dominated Catchments

Abstract: Spatiotemporal information on historical peatland drainage is needed to relate past land use to observed changes in catchment hydrology. Comprehensive knowledge of historical development of peatland management is largely unknown at catchment scale. Aerial photos and LIDAR data enlarge the possibilities for identifying past peatland drainage patterns. Here, our objectives are: (1) to develop techniques for semi-automatically mapping the location of ditch networks in peat-dominated catchments by using aerial pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Still, it will be worth exploring whether adding more indices besides HPMF can improve the prediction accuracy. For example, a recent study in Finland by Bhattacharjee et al (2021) demonstrated that aerial photos may contain important information for mapping drainage ditches on peatlands. However, in areas hidden beneath canopy, it might be better to include topographical indices such as impoundment size index implemented in Whitebox tools 1.4.0 (Lindsay 2018), which can be included as multiband images.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it will be worth exploring whether adding more indices besides HPMF can improve the prediction accuracy. For example, a recent study in Finland by Bhattacharjee et al (2021) demonstrated that aerial photos may contain important information for mapping drainage ditches on peatlands. However, in areas hidden beneath canopy, it might be better to include topographical indices such as impoundment size index implemented in Whitebox tools 1.4.0 (Lindsay 2018), which can be included as multiband images.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for a river catchment level hydrology analysis, the knowledge of watercourse network expansion, both downstream and upstream, is needed (Bhattacharjee et al. 2021 ). Such knowledge of drainage systems is also of importance for the assessment of maintenance needs or candidate mires for restoration (Hasselquist et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the coarse spatial resolution of old satellite images and the inability to detect features below the canopy layer in satellite and aerial images limit their utilization in mapping linear features (Bhattacharjee et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous ditch studies utilizing LiDAR-derived DEM have mapped smaller areas up to 150 ha (Cazorzi et al 2013 ; Rapinel et al 2015 ; Roelens et al 2018a ) while we mapped 1708 km of ditches and 248 km of natural streams in 11 study regions covering a total of 415 km 2 . Only recently, Bhattacharjee et al ( 2021 ) conducted a ditch detection analysis in a large forested peatland in Finland; this study was highly reliant on aerial imagery, and notable uncertainties were reported when aerial images were unavailable for parts of the study area. While the strength of manual interpretation of high-resolution DEM for ditch detection was demonstrated in this study, we also highlight the extensive investment of man-hours for manual digitization.…”
Section: Discussionmentioning
confidence: 99%